If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 143 + -3X = 24X + 23 Reorder the terms: 143 + -3X = 23 + 24X Solving 143 + -3X = 23 + 24X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-24X' to each side of the equation. 143 + -3X + -24X = 23 + 24X + -24X Combine like terms: -3X + -24X = -27X 143 + -27X = 23 + 24X + -24X Combine like terms: 24X + -24X = 0 143 + -27X = 23 + 0 143 + -27X = 23 Add '-143' to each side of the equation. 143 + -143 + -27X = 23 + -143 Combine like terms: 143 + -143 = 0 0 + -27X = 23 + -143 -27X = 23 + -143 Combine like terms: 23 + -143 = -120 -27X = -120 Divide each side by '-27'. X = 4.444444444 Simplifying X = 4.444444444
| 2(5x-4)=2(19x+16) | | y-6/6=8 | | 7n+5=5(n+5) | | -1,5x-2=9,5 | | x+12x+20= | | 4(x+5)=38 | | 12-3x=24+x | | 3125+-100x+x^2=0 | | 28x=24 | | -6(2x-1)+3=-12x+9 | | p/3=4 | | 2.5x^2+0.6x=3480 | | x+13x+40= | | 8x-6=8(x+6) | | 9x-2y=0 | | 1/2x+1/4y=12 | | 2(2x+6)=4x+12 | | 3n-2=6-n | | 5x^2=3+2x | | x+3=10x | | 0.8x-2.6=1.7x+1.5 | | x+11x+8= | | 5m+1=13-m | | 1/2x+1/4=12 | | 0.12(y-7)+0.06y=0.02y-1.8 | | 4t-3=t+9 | | x+13x+30= | | -(x-1)=-2(-x-1)-4 | | X/6x-1=5 | | 3x^2=3+8x | | X/6x-1=5/1 | | x+11x+28= |